Assessment of awareness of oral cancer among nursing students at BPKIHS, Nepal - Keshwar, Shashi; Sarraf, Deependra Prasad; Shrestha, Ashish; Karn, Basant Kumar (Journal of Chitwan Medical College, 2020)
Background: Early recognition of oral cancer is essential for higher cure rate and better prognosis. Nurses can play a significant role in the early diagnosis of cancers. The study aimed to assess the awareness of oral cancer among nursing students. Methods: A cross-sectional survey was conducted among Bachelor of Nursing Students at College of Nursing, B.P. Koirala Institute of Health Sciences. A semi-structured questionnaire was used to collect the sociodemographic data and awareness of cancer. Descriptive statistics were calculated using Statistical Package for Social Sciences version 22.0. Results: Out of 116, 89 (76.7%) students were of age 21-25 years. One hundred and twelve students (96.6%) were aware that various form of tobacco increases risk of oral cancer; however, only 55 (47.4%) students knew alcohol drinking as a risk factor. Only 29 (25.0%) students were aware of loose-fitting denture as a risk factor for oral cancer. Ninety-six (82.8%) students knew white or red patch as possible signs of oral cancer; however, only six (5.2%) students were aware of the most common site of oral cancer. Only 16 (13.8%) students considered that they are adequately trained to screen oral cancer. One hundred and fifteen (99.1%) students demanded more education on oral cancer. Conclusions: This study revealed that nursing students’ awareness of risk factors and the importance of screening of oral cancer is suboptimal. It highlights a need for basic education on oral cancer to make them more aware and further competent toward oral cancer screening and referral.